Analisis Korelasi Kadar Hemoglobin Dengan Riwayat Lama Menderita Diabetes Mellitus Tipe 2 - Nuari, Nian Afrian (Fakultas Ilmu Kesehatan, 2021)
Diabetes mellitus is a metabolic disease that has characteristics of high blood sugar levels (hyperglycemia), this can occur due to abnormalities in insulin secretion. The aim of this study was to determine the relationship of hemoglobin levels with long suffering Diabetes Mellitus patients. This study used was correlational design with a cross sectional approach. The population in this study were 225 people with a sample of 67 respondents with purposive sampling technique. Data was collected by checking hemoglobin levels and Quesioner. The results showed that almost all respondents had normal hemoglobin levels and most of the respondents had long history of suffering from Diabetes Mellitus for 5-10 years.. Data analysis used was the Rho Spearman test and can not found the relationship between hemoglobin levels and long suffering Diabetes Mellitus (p value = 0.565). History of suffering from Diabetes Mellitus,did not necessarily have low hemoglobin levels, because it can be noticed from other factors such as routine taking medication, diet, exercise, and lifestyle that can affect the condition of diabetes patients themselves. Diabetes Mellitus patients need to maintain the blood sugar levels and hemoglobin levels with a healthy lifestyle, take the recommended diet, routinely consume drugs, and check blood sugar levels regularly.